Quality of match for statistical matches used in the development of the Levy Institute measure of time and income poverty (LIMTIP) for Argentina, Chile and Mexico - Thomas Masterson (Levy Economics Institute of Bard College, 2011)
The quality of match of three statistical matches used in the LIMTIP estimates for Argentina, Chile, and Mexico is described. The first match combines the 2005 Uso del Tiempo (UT 2005) with the 2006 Encuesto Annual de Hogares (EAH) for Argentina. The second match combines the 2007 Encuesta Experimental sobre Uso del Tiempo en el Gran Santiago (EUT 2007) with the 2006 Encuesta Caracteristización Socioeconómica Nacional (CASEN 2006) for Chile. The third match combines the 2008 Encuesta Nacional de Ingresos y Gastos de los Hogares (ENIGH 2008) with the 2009 Encuesta Nacional sobre Uso del Tiempo (ENUT 2009) for Mexico. In each case, the alignment of the two datasets is examined, after which various aspects of the match quality are described. In each case, the matches are of high quality, given the nature of the source datasets.
Keywords: C14; C40; D31; J22; 330; statistical matching; time use; household production; poverty; LIMTIP; Argentina; Chile; Mexico